Prospek Statistik Nonparametrik Metode Brown-Mood dalam Pendidikan Tinggi: Suatu Aplikasi dalam Regresi Linier Sederhana - mutijah mutijah (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Purwokerto, 2015)
: This paper has been used to give insight for the researches or the students of high school about nonparametric statistic and itâ€™s applications at the analysis of simple regression specially to fit the regression line and the test of hypotheses. A regression line of estimation Y = a + bX, in nonparametric statistic a and b can be found way of manual with least square method. But in nonparametric statistic can be found way of manual with Brown-Mood method. The test of hypotheses for a and b from population with model of regression equalization Y = a + bX is used Brown-Mood method too. The statistic of test from Brown-Mood method as follow : x2 = with n, n1, and n2Â follow steps from Brown-Mood.Â